Pengaruh Current Ratio, Return on Asset, Debt to Equity Ratio dan Firm Size terhadap Price to Book Value pada Perusahaan Consumer Cyclicals Subsektor Apparel and Luxury Goods yang Terdaftar di Bursa Efek Indonesia Periode 2015-2023 - Indasyah, Muhammad Wisnu; Syarif, Devyanthi (Masyarakat Ekonomi Syariah Bogor, 2024)
The purpose of this research is to ascertain how the price to book value of consumer cyclical companies in the apparel and luxury goods subsector listed on the Indonesia Stock Exchange is affected by return on assets, current ratio, debt to equity ratio, and business size between 2015 and 2023. An approach to verification and description is combined with a quantitative methodology in this study. Statistical tests for verification include the traditional assumption test, multiple linear regression, Pearson correlation coefficient, determination coefficient, and hypothesis testing with partial and simultaneous tests (t and f tests). The Financial Reports of 72 Companies in the Apparel and Luxury Goods Subsector of Consumer Cyclicals Companies provide the sample data. sampling with nonprobability purposive sampling. Version 26.0 of SPSS is utilized as a data processing tool. Price to Book Value is not impacted in any way by the study's findings regarding Current Ratio, Return on Asset, Debt to Equity Ratio and firm size. The study's findings concurrently demonstrated that Price to Book Value was significantly impacted by Current Ratio, Return on Asset, Debt to Equity Ratio, and Company Size